The impact of advertisements on donation behavior amongst graphic student in UiTM / Muhammad Faiz Aswan Fesal - Aswan Fesal, Muhammad Faiz (Faculty of Art and Design, 2013)
This research entitled The Impact of Advertisements on Donation Behavior Amongst Graphic Student in was carried out in order to meet certain objectives. The research focuses a graphic students from the Faculty of Art and Design, UiTM Shah Alam. As we all know that campaign or promoting a brand require a lot of effort, time and money in order to well-educate the public of the existence of a campaign and maybe reinforce brand recall to establish a good image between a brand and the audience. However, taking decision on fundraising is the most difficult tasks facing many business executives. This is because it is difficult to predict, estimate or determine with accuracy, potential donators demands as they are uncontrollable factors external to an organization. Considering, therefore, the importance of fundraising on charity campaign and the connection between donators and fundraising, it is expedient for organizations to engage in programmes that can influence donators’ decision to donate into the donation box. This is where advertising and brand management are relevant. Advertising is a subset of promotion mix which is one of the 4ps in the marketing mix that consist of product, price, place and promotion. As a promotional strategy, advertising serve as a major tool in creating campaign awareness and condition the mind of a potential donaters to take eventual purchase decision. It is important for organisation to know whether their advertisements are effective or not, in order to check the impact of the advertisements.